2020
DOI: 10.34172/hpp.2020.40
|View full text |Cite
|
Sign up to set email alerts
|

Communicating health crisis: a content analysis of global media framing of COVID-19

Abstract: Background: This study examines the global media framing of coronavirus disease 2019 (COVID-19) to understand the dominant frames and how choice of words compares in the media. Periods of health crisis such as the outbreak of coronavirus pandemic add to the enormous burden of the media in keeping people constantly informed. Extant literature suggests that when a message is released through the media, what matters most is not what is said but how it is said. As such, the media could either mitigate or accentuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
135
1
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(163 citation statements)
references
References 21 publications
(37 reference statements)
6
135
1
21
Order By: Relevance
“…Ogbodo and colleagues (2020) examined media reporting from America, Africa, Asia and Europe and noted relatively similar representations of the COVID-19 pandemic through the prism of economic and ethnic issues, as well as through conflict and fear-mongering frames. However, there were some notable differences as the frames of hope and morality were more prominent in the Vatican's media, the human interest frame was more frequent in America and Europe, while the politicisation frame was mostly used by Chinese media (Ogbodo et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Ogbodo and colleagues (2020) examined media reporting from America, Africa, Asia and Europe and noted relatively similar representations of the COVID-19 pandemic through the prism of economic and ethnic issues, as well as through conflict and fear-mongering frames. However, there were some notable differences as the frames of hope and morality were more prominent in the Vatican's media, the human interest frame was more frequent in America and Europe, while the politicisation frame was mostly used by Chinese media (Ogbodo et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Firstly, the article has demonstrated that online reviews can reliably be used to understand travellers' reflections during a crisis using text mining. Furthermore, instead of reviews that are filled with the undesirable impacts of COVID-19, such as fear or scaremongering (Ogbodo et al, 2020) or trip cancellations (Uğur & Akbıyık, 2020) or the origin of the virus and its sources (Abd-Alrazaq et al, 2020), this article is filled with more positive and generalised comments on travel in Botswana. Comments specific to COVID-19 such as trip disruptions and limited service or fear and anxiety were very limited.…”
Section: Conclusion and Recommendations For Further Studymentioning
confidence: 99%
“…Можно предположить, что в случае с пандемией COVID19 эти сложности в организации массовой коммуникации также наблюдались. Например, согласно отдельным исследованиям, характер дискуссии по данному вопросу мог повышать тревожность населения [Ogbodo et al, 2020]. Кроме того, освещение проблемы неоднократно изменялось в ответ на поступление новой информации, введение тех или иных ограничительных мер и т. д. Образ коронавируса в период, когда он еще не пришел в Россию, во время самоизоляции и в момент снятия ос новных ограничений существенно различался.…”
Section: теоретическая основа и проблема исследованияunclassified